5x+9y-6=0

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Move all terms not containing y to the right side of the equation.

Subtract 5x from both sides of the equation.

9y-6=-5x

Add 6 to both sides of the equation.

9y=-5x+6

9y=-5x+6

Divide each term by 9 and simplify.

Divide each term in 9y=-5x+6 by 9.

9y9=-5×9+69

Cancel the common factor of 9.

Cancel the common factor.

9y9=-5×9+69

Divide y by 1.

y=-5×9+69

y=-5×9+69

Simplify each term.

Move the negative in front of the fraction.

y=-(5)x9+69

Cancel the common factor of 6 and 9.

Factor 3 out of 6.

y=-5×9+3(2)9

Cancel the common factors.

Factor 3 out of 9.

y=-5×9+3⋅23⋅3

Cancel the common factor.

y=-5×9+3⋅23⋅3

Rewrite the expression.

y=-5×9+23

y=-5×9+23

y=-5×9+23

y=-5×9+23

y=-5×9+23

Rewrite in slope-intercept form.

y=-59x+23

y=-59x+23

Using the slope-intercept form, the y-intercept is 23.

b=23

Find the Y-Intercept 5x+9y-6=0